2006
DOI: 10.1203/01.pdr.0000220349.41675.92
|View full text |Cite
|
Sign up to set email alerts
|

Cognition- and Anxiety-Related Behavior, Synaptophysin and MAP2 Immunoreactivity in the Adult Rat Treated with a Single Course of Antenatal Betamethasone

Abstract: ABSTRACT:We investigated the effects of a single course of antenatal betamethasone on cognition-and anxiety-related behavior and synaptophysin and microtubule-associated protein 2 (MAP2) immunoreactivity in the adult rat hippocampus. On d 20 of gestation, pregnant rats were injected with either 1) 170 g/kg body weight of betamethasone ("clinically equivalent dose," equivalent to 12 mg twice, 24 h apart); 2) half this dose; or 3) vehicle. Cognition-and anxiety-related behavior of the offspring was analyzed at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…Additionally, the fact that anxious behaviors in the MB test were detected at the early post‐weaning age (P22) suggests that this test may be more sensitive to detecting anxiety‐like states in rodents compared with the EPM. On the contrary, Bruschettini et al (2006) using a similar animal model report no harmful effects of prenatal BET administration (a single course of BET, 170 μg kg −1 ) on anxiety‐like behavior. This discrepancy could be explained by differences in the tests used (open field versus EPM/MB employed in the current study) and the animals' age analyzed (P150 versus P22/52/82).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the fact that anxious behaviors in the MB test were detected at the early post‐weaning age (P22) suggests that this test may be more sensitive to detecting anxiety‐like states in rodents compared with the EPM. On the contrary, Bruschettini et al (2006) using a similar animal model report no harmful effects of prenatal BET administration (a single course of BET, 170 μg kg −1 ) on anxiety‐like behavior. This discrepancy could be explained by differences in the tests used (open field versus EPM/MB employed in the current study) and the animals' age analyzed (P150 versus P22/52/82).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, studies carried out in sheep demonstrated that prenatal BET produced significant decreases in the brain cytoskeletal microtubule‐associated proteins (MAPs) and the presynaptic marker protein synaptophysin (Antonow‐Schlorke et al, 2003). Considering that Purkinje cell dendritic outgrowth and maintenance depends in part on the expression of the cytoskeletal microtubule associated protein 2 (MAP2; Goodlett et al, 1990; Teng et al, 2001; Tucker et al, 1988), the first objective of the present study was to determine whether prenatal betamethasone administration (170 μg kg −1 , twice during gestational day 20, G20; Bruschettini et al, 2006; Scheepens et al, 2003) alters the immunohistochemical expression of MAP2 at three relevant postnatal stages, i.e., the post‐weaning (P22), adolescence (P52) and young adult (P82) stages in rats. Also, since brain‐derived neurotrophic factor (BDNF) significantly contributes to Purkinje cell differentiation, the second objective was to assess the deleterious impact of prenatal BET administration on BDNF and its high‐affinity tyrosine kinase B (TrkB) receptor expression (Goodlett et al, 1990; Tucker et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…We used this procedure because it is equivalent to that employed in the obstetrical clinic (two doses every 24 hours, 12 mg per dose). 8 Day G20 was chosen because it corresponds to the approximate ontogenetic stage of a human preterm fetus (24-32 weeks' gestation). CON group received an equal volume (1 mL) of normal saline.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Considering that various studies have reported that antenatal exposure to sGC decreases postnatal weight, 8,15 we measured the body and brain weights of the animals at birth (P0), "infancy" (P22), and "adolescence" (P52).…”
Section: Body and Brain Weightmentioning
confidence: 99%
See 1 more Smart Citation